Method for the use of polymer beads as dosimeters for low-energy electron irradiation - Besecke, Joana Kira; Kenner, Lysann; Poremba, André; Schönfelder, Jessy; Teichmann, Tobias; Thoma, Martin; Grunwald, Thomas; von Hauff, Elizabeth; König, Ulla; Poppe, Björn; Schopf, Simone (Frontiers in Physics, 2024)
In this study, a novel bead-based dosimetry system was developed. This approach uses suspended polymethyl methacrylate beads, which experience a dose-dependent change in fluorescence intensities. The beads were diluted in deionized water and exposed to low-energy electron irradiation. Afterward, the beads were analyzed by flow cytometry. The mean fluorescence of these beads increased with the radiation dose in the range of 10–50 kGy. Thus, flow cytometric fluorescence measurements allow dose mapping: the signal of each bead could be assigned to a corresponding dose. The correlation between the dose and fluorescence intensity of the beads was previously examined by irradiation using a high-energy electron beam. The presented method shows potential for dosimetry in liquids for quality control in biotechnological or pharmaceutical applications using low-energy electron irradiation as the method is easy to handle, not limited to solid-state geometry, and suitable for static and dynamic irradiation setups of liquids. This novel method provides information about the dose distribution in the investigated volume of liquid by analyzing individual beads. This provides information about average, minimum, and maximum dose values, as well their actual distribution function, which is a big advantage over other methods of liquid dosimetry, where only the mean value can be obtained.